Epidemiological profile of reported road traffic accident cases to emergency medicine department of a teaching medical college in South Karnataka - Kundu, Rituparna; Manjunath, Renuka; Srinivasarangan, Madhu; R. C., Manish (International Journal Of Community Medicine And Public Health, 2024)
Background: The study delves into the pressing issue of Road Traffic Accidents, a significant public health concern worldwide, particularly in low- and middle-income nations. With the backdrop of the 2030 Agenda for Sustainable Development, road safety has gained paramount importance. This research aims to comprehensively examine the multitude of factors influencing RTAs by analyzing data sourced from individual interviews, case summaries, and medico-legal records from a tertiary care hospital's Emergency Medicine Department. Methods: A hospital-based cross-sectional study conducted at JSS hospital, Mysuru. Data from 1525 retrospective cases spanning (2019-2021) and 114 prospective cases from December 2022 to January 2023 were analyzed. A pre-tested, semi-structured proforma gathered socio-demographic variables, etc. Analysis revealed a surge in accidents in 2021 compared to previous years, with a majority occurring between 8 pm to 8 am. Primarily in the 21-30 years age group. Over the three-year period, 72 fatalities were recorded, predominantly among males. Results: The study identified significant associations between RTAs and factors such as gender, vehicle type, mode of transportation, and referring hospital. Lower education levels correlated with increased risk, highlighting the importance of road safety education. Additionally, a striking urban-rural disparity was noted, with majority of RTAs occurring in rural areas. Conclusions: Overall, this study underscores the complex nature of RTAs and highlights the importance of addressing multiple risk factors to effectively mitigate road traffic injuries. By understanding these factors, policymakers and healthcare professionals can develop targeted interventions aimed at reducing the burden of RTAs and promoting safer road practices.